A Digital Twin Trust Framework for Industrial Application. (May 2022) - Trauer, J.; Schweigert-Recksiek, S.; Schenk, T.; Baudisch, T.; Mörtl, M.; Zimmermann, M.
Abstract: A reason for the slow adoption of digital twins in industry is a lack of trust in the concept and between the stakeholders involved. This paper presents a Trust Framework for Digital Twins based on a literature review and an interview study, including seven recommendations: (1) explain your twin, (2) create a common incentive, (3) make only one step at a time, (4) ensure IP protection and IT security, (5) prove your quality, (6) ensure a uniform environment, and (7) document thoroughly. Together with 20 concrete measures it supports practitioners in improving trust in their Digital Twin.